1998
DOI: 10.1016/s0002-9440(10)65707-0
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of CD99 Induces Apoptosis Through a Calcineurin-Independent Pathway in Ewing's Sarcoma Cells

Abstract: Programmed cell death (PCD) is a prominent feature of the development of the immune and nervous systems. In both systems, widespread PCD occurs in primitive progenitor cells during development. In this study, we demonstrated that Ewing's sarcoma (ES) cells, undifferentiated neural precursors, underwent apoptosis upon engagement of CD99 with anti-CD99 monoclonal antibody. Apoptosis via CD99 occurred only in the undifferentiated state of ES cells, but not in differentiated ES cells. CD99-induced apoptosis in ES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 27 publications
2
68
1
1
Order By: Relevance
“…In the present case, the primary tumor did not express keratin but the xenograft was reactive with keratin. This result supports that Ewing's sarcoma may represent the stage of either very early pluripotential cells or primitive neuroectodermal cells that can differentiate along a neuronal, glial, Schwannian, melanocytic, neuroendocrine, or even ectomesenchymal pathway (Sohn et al 1998).…”
supporting
confidence: 79%
“…In the present case, the primary tumor did not express keratin but the xenograft was reactive with keratin. This result supports that Ewing's sarcoma may represent the stage of either very early pluripotential cells or primitive neuroectodermal cells that can differentiate along a neuronal, glial, Schwannian, melanocytic, neuroendocrine, or even ectomesenchymal pathway (Sohn et al 1998).…”
supporting
confidence: 79%
“…Recent reports demonstrate that, in the absence of caspase activity, other apoptotic events, such as phosphatidylserine (PS) externalisation to the cell surface, mitochondrial alterations, membrane blebbing, cell shrinkage and nuclear condensation/fragmentation can still occur. [148][149][150][151][152][153] The activity of the caspases can be inhibited by the synthetic peptide Ac-DEVD-CHO, which mimics the recognition site in PARP, a caspase-3 substrate. 154 Interestingly, the hsp70 molecule has a conserved C-terminal sequence -EEVD.…”
Section: Figurementioning
confidence: 99%
“…In pathological conditions, the triggering of CD99 results in the induction of cell-cell adhesion and apoptosis of Ewing's sarcoma cells (Sohn et al, 1998;Scotlandi et al, 2000;Cerisano et al, 2004). Moreover, it has recently been found that CD99 downregulation is essential in osteosarcoma to express full malignancy (Manara et al, 2006).…”
Section: Introductionmentioning
confidence: 99%